ChemInform Abstract: Synthesis of Various Saturated and Unsaturated N‐Heterocyclic Carbene Precursors by Triflic Anhydride Mediated Intramolecular Cyclization. Issue 29 (1st July 2013) - Zhang, Jun; Fu, Jun; Su, Xiaolong; Wang, Xiao; Song, Shangfei; Shi, Min
Abstract: A facile and versatile method for the synthesis of the title N‐heterocyclic carbenes including ones which are not accessible by using previously published methods, e.g. (XIII), is presented.